COMPOSITION OF THE UPPER MANTLE UNDER THE UDOKAN RANGE IN THE NORTHEASTERN PART OF THE BAIKAL RIFT ZONE - Turkov V.A.; Kogarko L.N.; Kolesov G.M.; Shubina N.A.; Ryabchikov I.D.; Polyakov A.I.; Ignatenko K.I. (My University, 1988)
Geochemical study of plutonic xenoliths from different regions of the world not only allows the composition of the lithosphere there to be estimated, but also enables the evolution of the upper mantle during geologic time to be traced, and the trends of its vertical and lateral variation to be better understood. Therefore, to continue previous research on the composition of the upper mantle under central Asia, we studied plutonic xenoliths from the Udokan Range. Volcanic rocks of the Udokan Range on the northeast flank of the Baikal rift zone are the most differentiated of all Neogene-Quaternary extrusives in this zone. Our work has revealed the mixed composition and complex history of the lithosphere under the Baikal rift zone. Besides little-altered blocks (primary, 'undifferentiated material'), there are sections that underwent different degrees of partial melting (xenoliths depleted in 'basaltic' components), as well as zones of metasomatic reworking, which led to enrichment of rocks in light REE.
Keywords: Quaternary; Neogene; Кайнозой::Неоген; Cenozoic::Neogene; Cenozoic::Quaternary; Кайнозой::Четвертичная